Study of the mass and spin-parity of the Higgs boson candidate via its decays to Z boson pairs. - Chatrchyan, S; Khachatryan, V; Sirunyan, A; Tumasyan, A; Adam, W; Aguilo, E; Bergauer, T; Dragicevic, M; Erö, J; Fabjan, C; Friedl, M; Frühwirth, R; et al. (2013)
A study is presented of the mass and spin-parity of the new boson recently observed at the LHC at a mass near 125 GeV. An integrated luminosity of 17.3 fb(-1), collected by the CMS experiment in proton-proton collisions at center-of-mass energies of 7 and 8 TeV, is used. The measured mass in the ZZ channel, where both Z bosons decay to e or μ pairs, is 126.2 ± 0.6(stat) ± 0.2(syst) GeV. The angular distributions of the lepton pairs in this channel are sensitive to the spin-parity of the boson. Under the assumption of spin 0, the present data are consistent with the pure scalar hypothesis, while disfavoring the pure pseudoscalar hypothesis.